Solid medical waste management system at the Regional General Hospital (RSUD) Puri Husada Tembilahan 2023 - Fitri, Jufenti Ade; Fitriani, Fitriani; Randika, Rendi; Meri, Dilgu (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Hospital is a health service institution with preventive, curative, rehabilitative and promotive service activities. Hospital solid medical waste contains hazardous materials (infectious, toxic and radioactive) if not managed properly it can pollute the environment and is considered a link in the chain of spread of infectious diseases. This study aims to look at the solid medical waste management system at the Puri Husada Tembilahan Regional General Hospital. This research is a qualitative research with a research design using observation design. This research was conducted in January-May 2023 at the Puri Husada Tembilahan Regional General Hospital (RSUD). The informants in this study were 1 head of non-medical support, 1 person in charge of environmental sanitation, 1 nurse, 1 person of tps lb3 and a cleaning officer. The instruments in this study used observation sheets and interviews. Data analysis was carried out by means of data reduction, data presentation and drawing conclusions. Inadequate human resources (HR). Standard operating procedures (SOP) at Puri Husada Tembilahan Hospital already exist and are on the way. The Operational Fund for the management of solid medical waste is taken from the capitation fund. The facilities and infrastructure used when managing solid medical waste are safety boxes and trash cans. The stages of sorting, storing and transporting solid medical waste are still not appropriate according to PermenLHK No. 56 of 2015, but the collection stage already meets the requirements of PermenLHK No. 56 of 2015. medical solid waste management at Puri Husada Tembilahan Hospital is not in accordance with the provisions of PermenLHK No. 56 of 2015. Waste management efforts need to be guided by the provisions of PermenLHK No. 56 of 2015. Keywords: Solid Medical Waste Management, Environment